Rearrangement and expression of the immunoglobulin μ-chain gene in human myeloid cells - Huang, Jing (Nature Publishing Group, 2014)
Immunoglobulin (Ig), a characteristic marker of B cells, has been reported to be expressed in epithelial cells, with a suggested role in their growth and survival. We have previously reported that IgG heavy chain is expressed in acute myeloid leukemia (AML), but not in the monocytes or neutrophils from patients with non-hematopoietic neoplasms or healthy controls. In the present study, we assessed IgM heavy chain expression and repertoire in human myeloid cells. We detected V(Hμ)DJ(Hμ) rearrangement and expression in 7/7 AML cell lines, 7/14 primary myeloblasts from AML patients, and interestingly, 8/20 monocytes and 3/20 neutrophils from patients with non-hematopoietic neoplasms and healthy individuals. We also found evidence of somatic hypermutation of the variable (V) gene segments in AML-derived IgM gene rearrangements but not in IgM from monocytes or neutrophils from patients with non-hematopoietic neoplasms and healthy individuals. Furthermore, IgM V(Hμ)DJ(Hμ) gene rearrangements in AML cell lines, primary myeloblasts, and monocytes and neutrophils from patients with non-hematopoietic neoplasms showed a restricted V usage and repertoire, whereas the V(Hμ)DJ(Hμ) gene rearrangements in monocytes and neutrophils from healthy individuals displayed more diversity. Anti-human IgM inhibited cell proliferation, but did not induce apoptosis in AML cell lines. Our findings suggest that AML-derived IgM might be a novel AML-related molecule that is involved in leukemogenesis and AML progression and might serve as a useful molecular marker for designing targeted therapy and monitoring minimal residual disease.